Armored Brain, Giant Calcified Chronic Subdural Hematoma, in 97-Year-Old Patient: Systematic Review - Khelifa, Adel; Abbassi, Omran; Bennafaa, Toufik; Aichaoui, Fayçal; Abdelhalim, Morsli (Asian Journal of Neurosurgery, 2025)
Calcified chronic subdural hematoma (CCSDH) is a rare neurosurgical entity. Due to limited reported cases, its diagnosis and management remain poorly understood. This study aims to enhance the understanding of CCSDH and improve familiarity with its clinical presentation, imaging features, and treatment strategies. A comprehensive search was performed using PubMed, Scopus, DOAJ (Directory of Open Access Journals), BASE (Bielefeld Academic Search Engine), and ScienceDirect with the keyword “calcified chronic subdural hematoma,” without date restrictions. Out of 354 articles initially identified, 163 unique records remained after merging duplicates. Following abstract and full-text screening, 76 articles describing 93 cases were included. One additional case from our institution was added, resulting in 94 cases reviewed. The average patient age was 41.88 years, with a strong male predominance (sex ratio 4.53). No past medical history was noted in 24 cases; ventriculoperitoneal shunt was present in 33 cases. While 14% were asymptomatic, 34% presented with intracranial hypertension, 12.5% with altered consciousness, 33% with motor deficits, and 25.5% with seizures. Bilateral CCSDH was observed in 21 patients, totaling 115 hematomas. Imaging showed: capsule-only calcification (52%), total (28%), or partial (20%) calcification. Hematoma shapes were biconvex (37%), concave (29%), bean-like (20%), irregular (7%), and thin lamina (6%). Computed tomography (CT) was used in 90.5%, and magnetic resonance imaging in 43.6%. Twenty-seven were visible on plain X-ray. Twenty cases were managed conservatively; two later required surgery. About 70 surgical procedures were performed: 60 via craniectomy, 9 burr holes procedures, and 1 via twist drill. Outcomes were favorable in 75% of conservatively treated cases and 87.5% of craniectomy cases. Six surgical deaths occurred. CCSDH primarily affects young males, often with a history of shunting. CT remains the imaging modality of choice. Conservative treatment is suitable for noncompressive, asymptomatic cases, while surgical evacuation via craniectomy offers the best outcomes when intervention is required.
Keywords: armored or armored brain; calcified subdural hematoma; chronic subdural hematoma; calcified empyema; epilepsy